2013
DOI: 10.1187/cbe.12-08-0133
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped: Investigating Gender in Introductory Science Courses

Abstract: This study investigated the performance of women and men across introductory science courses, stereotype threat endorsement, and the utility of a values-affirmation writing task in reducing achievement gaps. Data analysis revealed no achievement gap, little stereotype threat endorsement, and no impact of the values-affirmation writing task on performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 54 publications
4
56
2
1
Order By: Relevance
“…Few genetics studies have considered potential biases in measures of understanding, and none of those that we reviewed (see Table 1) have provided a cross-cultural or multi-level perspective as a source of generalization validity. Notably, our findings differ from other American studies documenting a male advantage in biology at the undergraduate level (Eddy et al 2014;Stanger-Hall 2012;Wright et al 2016), but are similar to Dogru-Atay and Tekkaya's (2008) study of middle schoolers, which also showed no gender advantage on multiple-choice inheritance items, and several other studies finding no gender bias (Dimitrov 1999;Huppert et al 2002;Lauer et al 2013;Schroeders et al 2013;Shepardson and Pizzini 1994;Willoughby and Metz 2009). While few studies have examined racial or ethnic differences in biology achievement, those that have (Creech and Sweeder 2012;Dimitrov 1999) found no impact, which is in alignment with our findings.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Few genetics studies have considered potential biases in measures of understanding, and none of those that we reviewed (see Table 1) have provided a cross-cultural or multi-level perspective as a source of generalization validity. Notably, our findings differ from other American studies documenting a male advantage in biology at the undergraduate level (Eddy et al 2014;Stanger-Hall 2012;Wright et al 2016), but are similar to Dogru-Atay and Tekkaya's (2008) study of middle schoolers, which also showed no gender advantage on multiple-choice inheritance items, and several other studies finding no gender bias (Dimitrov 1999;Huppert et al 2002;Lauer et al 2013;Schroeders et al 2013;Shepardson and Pizzini 1994;Willoughby and Metz 2009). While few studies have examined racial or ethnic differences in biology achievement, those that have (Creech and Sweeder 2012;Dimitrov 1999) found no impact, which is in alignment with our findings.…”
Section: Discussioncontrasting
confidence: 57%
“…In biology education, the roles of gender and ethnicity on domain-specific performance remain unsettled. Some studies, for example, have documented the absence of significant gender effects on biology performance (e.g., Dimitrov 1999;Huppert et al 2002;Lauer et al 2013;Schroeders et al 2013;Shepardson and Pizzini 1994;Willoughby and Metz 2009). Dimitrov (1999) and Creech and Sweeder (2012) found no impact of ethnicity on biology performance, and Nehm and Schonfeld (2008) found similar types of alternative conceptions in underrepresented students as documented in other demographic groups.…”
Section: Demographic Factors and Genetics Educationmentioning
confidence: 99%
“…In the studies that do not control for ability, there is either no achievement gap or one in favor of females (Table I). This pattern holds true even within a discipline: in biology, the one study of introductory biology classes that did not use a control for student ability did not find an achievement gap [24], but our own work in introductory biology courses that controlled for student performance in their prior college classes found an achievement gap that favored males [14].…”
Section: A Academic Performancementioning
confidence: 67%
“…Research may also focus on underlying mechanisms that lead to observed gaps in participation. In the United States, one common explanation is stereotype threat, or the fear of conforming to a negative stereotype associated with one's social, racial, ethnic, or gender group (6,(39)(40)(41). For example, females tend to underestimate their math ability and overestimate how much ability is required to succeed at higher levels (42).…”
Section: Discussionmentioning
confidence: 99%